Effect of microbial biomass presence on palm shell activated carbon for the adsorption of Cu, Cd and Zn/ Gulnaziya Issabayeva - Issabayeva, Gulnaziya (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Concentration of heavy metals present in industrial wastewaters should be reduced to permissible discharge level to prevent their harmful environmental effect. Adsorption provides effective removal of metals from wastewater. Palm shell activated carbon (PSAC) and microbial biomass of Bacillus subtilis (BS) and Aspergillus niger (AN) are low cost adsorbents. Their ability to adsorb Cu(II), Cd(II) and Zn(II) ions from wastewater in batch mode was investigated in this study. Combination of PSAC with microbial biomass resulted in the decrease of pHpzc, surface area and porosity of the adsorbents compared to the original PSAC. However, the concentration of surface functional groups and negative charge density increased. Each biosorbent exhibited selective adsorption affinity. Thus, BS-PSAC showed highest sorption of zinc ions, 0.27mol/L; AN-PSAC showed the highest removal of copper, 0.51mol/L; and cadmium was best removed by original PSAC, 0.28mol/L. The adsorption capacity of the original and biomodified PSACs was higher at pH 5-6; positive ΔH° values indicated endothermic nature of adsorption process. Kinetics data showed that adsorption followed pseudosecond-order reaction model.Overall, the results demonstrated that modification of PSAC with microbial biomass selectively improved adsorption efficiency of heavy metals removal from wastewater.